Mining Concession Policy for Religious Organizations in Indonesia: An Analysis of Vertical Inconsistencies in the Norm Hierarchy Framework - Agung Barok Pratama; Aisyah Mutia Firdaus; Anindya Aryu Inayati; Nasrulhaq Nasrulhaq (UIN Sunan Kalijaga Yogyakarta, 2026)
This article examines inconsistencies in legal policies granting mining concessions to religious organizations in Indonesia. The legal issue is the inconsistency between Article 75, paragraph 3, of Law Number 3 of 2020 and Article 83A, paragraph 1, of Government Regulation Number 25 of 2024. The IUPK has been granted to a number of religious organizations that meet the qualifications, such as NU, Muhammadiyah, KWI, PHDI, and Walubi. This normative legal research uses legal and conceptual approaches, analyzing primary and secondary legal material through the study of documents and literature. The results of the study show that norm inconsistency arises from hyperregulation, the lack of harmonization of regulatory hierarchies, and sectoral egos in the legislative process. The legal implications include legal uncertainty, potential judicial review, loss of public trust, and confusion in the mining industry licensing process. This study contributes to understanding the normative inconsistencies between hierarchical legal regulations and their juridical implications, and provides recommendations for regulatory reform through strengthened harmonization and adherence to the principles of legislative hierarchy. The study's findings highlight the urgent need for regulatory alignment to ensure legal certainty and protect the public interest in the management of natural resources. Artikel ini mengkaji inkonsistensi kebijakan hukum yang memberikan konsesi pertambangan kepada organisasi keagamaan di Indonesia. Permasalahan hukum yang dihadapi adalah ketidaksesuaian antara Pasal 75 ayat 3 UU Nomor 3 Tahun 2020 dan Pasal 83A ayat 1 Peraturan Pemerintah Nomor 25 Tahun 2024. Pemberian IUPK telah diberikan kepada sejumlah organisasi keagamaan yang telah memenuhi kualifikasi seperti NU, Muhammadiyah, KWI, PHDI dan Walubi. Penelitian hukum normatif ini menggunakan pendekatan hukum dan konseptual, menganalisis materi hukum primer dan sekunder melalui studi dokumen dan literatur. Hasil penelitian menunjukkan bahwa inkonsistensi norma terjadi karena hiperregulasi, kurangnya harmonisasi hierarki regulasi, dan ego sektoral dalam proses legislasi. Implikasi hukum termasuk ketidakpastian hukum, potensi judicial review, hilangnya kepercayaan publik, dan kebingungan dalam proses perizinan industri pertambangan. Studi ini berkontribusi untuk memahami inkonsistensi normatif antara peraturan hukum hierarkis dan implikasi yuridisnya, memberikan rekomendasi untuk reformasi regulasi melalui proses harmonisasi yang diperkuat dan kepatuhan terhadap prinsip-prinsip hierarki legislatif. Temuan studi ini menyoroti kebutuhan mendesak untuk penyelarasan peraturan untuk memastikan kepastian hukum dan perlindungan kepentingan publik dalam pengelolaan sumber daya alam.